The Effectiveness of Program Keluarga Harapan in Kendal Regency - Karmelia Ardhyanti Nor Fauzin; Etty Soesilowati (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
The purpose of this study was to determine the implementation of the distribution and effectiveness of the program keluarga harapan in Kendal Regency as a poverty reduction program. This research uses mix method. The population of this study were all recipients of program keluarga harapan assistance with a sample of 100 respondents through purposive sampling technique. Analysis of the data is using descriptive analysis. The results showed that the variable of goal accuracy has not achieved the goal with a percentage value of 61.25%, the satisfaction variable with the program was obtained by being satisfied with the program with a percentage of 80.65% and the target accuracy variable obtained the target result was very precise with a percentage value of 61%. Suggestions related to this research are the need to immediately design technical guidelines for business assistance for the recipients, optimization of coaching by eliminating